Prefrontal hemodynamic activity predicts false memory—A near-infrared spectroscopy study - Kubota, Yasutaka; Toichi, Motomi; Shimizu, Mitsue; Mason, Richard A.; Findling, Robert L.; Yamamoto, Kokichi; Calabrese, Joseph R. (NeuroImage (Orlando, Fla.), 2006)
Evidence from lesion studies suggests an important role of the prefrontal cortex (PFC) in the reconstructive processes of episodic memory or memory distortion. Results from functional imaging studies imply PFC involvement during the illusionary recollection of non-experienced events. Here, we used a two-channel near-infrared spectroscopy (NIRS) system and conducted real-time monitoring of PFC hemodynamics, while subjects studied word lists and subsequently recognized unstudied items (false recognition). Bilateral increases in the oxygenated hemoglobin concentration ([oxy-Hb]) were observed during false recognition compared to true recognition, and a left PFC dominant increase of [oxy-Hb] was observed during encoding phases where subjects later claimed that they recognized unstudied words. Traces of semantic processing, reflected primarily in the left PFC activity, could eventually predict whether subjects falsely recognize non-experienced events.